COMPARATIVE STUDY OF SERUM LEPTIN, LIPID PROFILE AND FBG IN OVERWEIGHT, AND OBESE SUBJECTS IN NNEWI SOUTH-EAST NIGERIA - Nnamdi, Chinonso; Ubuo, Amah K; Anaelechi, Onuegbu J; Chima, Okpara H; Ekenedrichukwu, Okwara J; Madu, Olisekodiaka J; Akhaumere, Emmanuel O Akhaumere (Lux Mensana: Journal of Scientific Health, 2024)
Introduction. Obesity is caused by an imbalance between food intake and energy expenditure, leading to excessive fat accumulation in organs. Leptin, an adipokine, reflects adiposity and its levels increase with weight gain and decrease with weight loss. The purpose of this study was to compare of serum leptin, lipid profile and FBG in overweight. Methods. This is a cross-sectional study. A total of 90 healthy obese, overweight, and normal-weight participants who met the inclusion criteria were enrolled in the study. They were grouped using their body mass index of 18.5 to 24.9 kg/m2 (normal weight), 25 to 29.9 kg/m2 (overweight) and ≥30 kg/m2 (obese). The measured parameters were analyzed using standard methods. Results and Analysis. There was an increased difference in the mean level of Leptin (ug/l) of the obese participants compared to normal weight participants (0.63±0.29 vs 0.25±0.26, 0.001) and overweight when compared to normal weight (0.51±0.27 vs 0.25±0.26, 0.003). A significant positive correlation was observed when the leptin and BMI of obese subjects were compared. Mean fasting very low-density lipoprotein (VLDL) and triglyceride (TG) (mmol/l), were significantly higher (p<0.05) in overweight compared to normal weight participants (0.76±0.31 vs. 0.47±0.22) and (1.72±0.60 vs. 1.09±0.51) and obese participants (0.82±0.23 vs. 0.47±0.22) and (1.85±0.59 vs. 1.09±0.51) when compared to normal weight subjects respectively. Discussions. The level of leptin was increased in the overweight and obese groups when compared to the control groups and correlates positively with the BMI of the overweight and obese groups.